PENYULUHAN KELAS IBU HAMIL TENTANG P4K - Puspita, Yenni (JURNAL MEDIA KESEHATAN, 2018)
Birth Planning and Complication Prevention (P4K) Program with Stickers is an breakthrough effort in accelerating the decline in the death rate of mother and newborn baby. The Activity build on potential of the community, to preparation and save the mothers and newborn baby. Based on preliminary survey at clinic prumnas do researcher interview not structur to 8 pregnant women including two pregent women who have been putting up stickers P4K and 6 pregnant women have not planned and have not stick to P4K Stiker at home. Objective to know how the class counseling pregnant woment to knowledge and participation of expectant mother with the installation of the program on a p4k sticker. This type of research is Experimental design pre one group pretest-posttest . Samples taken by total sampling. The Data analysis do in univariat and bivariat wWilcon test at ? 5%. Research Result: that that the avererage Knowledge before to the counseling and after the counseling is There is difference of knowledge And participation of P4K sticker installation before and after the counseling in rejang lebong prumnas Bengkulu health center (p value = 0,000).